Effect of the inlet gas void fraction on the tip leakage vortex in a multiphase pump. (May 2020) - Shi, Guangtai; Liu, Zongku; Xiao, Yexiang; Yang, Hong; Li, Helin; Liu, Xiaobing
Abstract: Inlet gas void fraction (IGVF) played an important role on the flow characteristics in a multiphase pump. To reveal the effect of inlet gas void fraction on the flow characteristics in the tip clearance, a combination of numerical simulation and experiment was carried out and the reliability of numerical method was verified by comparing with the experimental data of the flow field by using high-speed photography. The results showed the accumulated gas was mainly at the impeller inlet near the pressure side (PS), tip clearance near the tip and the suction side (SS). When the IGVF increased, there was an obvious stratified structure and the separated vortex in the tip clearance. Compared to the water case, the gas caused the tip leakage flow velocity to decrease from the blade inlet to the streamwise coefficient of 0.2, and to increase from the streamwise coefficient of 0.2 to the blade trailing edge. At the same time, the IGVF had a significant influence on the tip leakage vortex (TLV) structure and trajectory, and the streamlines and vorticity distribution corresponding to the wake and the TLV were changed. Moreover, the flow characters and the structure of the TLV were more complicated under gas-liquid condition. Highlights: The numerical simulation was implemented under gas-liquid phase. The gas distribution and the flow characters in tip clearance were revealed. The variation of the tip leakage vortex structure was displayed. The vortex in diffuser corresponded to the minimum velocity.